1998
DOI: 10.1071/sb96024
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical studies in West Malaysian Icacinaceae

Abstract: On the basis of a comparative anatomical study of the leaf lamina and petiole of six genera of Icacinaceae in West Malaysia, these genera can be classified into four closely knit groups by virtue of their many shared characters: Group I comprises Cantleya, Gomphandra and Stemonurus whereas Groups II and III are made up of Gonocaryum and Sarcostigma, respectively. The climber genus Iodes is classified into Group IV. Taxonomically useful characters include the shape of the vascular bundles in both the midrib and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…n Data on crystals are mainly taken from Heintzelman and Howard (1948) and Teo and Haron (1999). l Normal hairs with a thin-walled based also have a thick-walled body.…”
Section: The Morphological and Total Evidence Analyses-mentioning
confidence: 99%
See 2 more Smart Citations
“…n Data on crystals are mainly taken from Heintzelman and Howard (1948) and Teo and Haron (1999). l Normal hairs with a thin-walled based also have a thick-walled body.…”
Section: The Morphological and Total Evidence Analyses-mentioning
confidence: 99%
“…m In the walls of these bulging base parts there are numerous pits. n Data on crystals are mainly taken from Heintzelman and Howard (1948) and Teo and Haron (1999). o For information on node and wood anatomy see Bailey and Howard (1941a, b, c, d), Howard (1943a), Sleumer (1971), Lozano-Contreras and de Lozano (1988), and Teo and Haron (1999).…”
Section: The Morphological and Total Evidence Analyses-mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, reports on Stemonuraceae showed that members of the family (Discophora, Gastrolepis, Lasianthera, Medusanthera and Stemonurus) have rhombic crystals. Also, other species such as Cantleya corniculata and Stemonurus malaccensis contain tannin crystals which are scattered in the mesophyll and ground tissue of the midrib [25]. Anisocytic stomata has been reported in L. africana [26].…”
Section: Discussionmentioning
confidence: 99%